Contribution of primary care expansion to Sustainable Development Goal 3 for health: a microsimulation of the 15 largest cities in Brazil. Issue 1 (11th January 2022) - Basu, Sanjay; Hone, Thomas; Villela, Daniel; Saraceni, Valeria; Trajman, Anete; Durovni, Betina; Millett, Christopher; Rasella, Davide
Abstract : Objectives: As middle-income countries strive to achieve the Sustainable Development Goals (SDGs), it remains unclear to what degree expanding primary care coverage can help achieve those goals and reduce within-country inequalities in mortality. Our objective was to estimate the potential impact of primary care expansion on cause-specific mortality in the 15 largest Brazilian cities. Design: Microsimulation model. Setting: 15 largest cities by population size in Brazil. Participants: Simulated populations. Interventions: We performed survival analysis to estimate HRs of death by cause and by demographic group, from a national administrative database linked to the Estratégia de Saúde da Família (Family Health Strategy, FHS) electronic health and death records among 1.2 million residents of Rio de Janeiro (2010–2016). We incorporated the HRs into a microsimulation to estimate the impact of changing primary care coverage in the 15 largest cities by population size in Brazil. Primary and secondary outcome measures: Crude and age-standardised mortality by cause, infant mortality and under-5 mortality. Results: Increased FHS coverage would be expected to reduce inequalities in mortality among cities (from 2.8 to 2.4 deaths per 1000 between the highest-mortality and lowest-mortality city, given a 40 percentage point increase in coverage), between welfare recipients and non-recipients (from 1.3 to 1.0 deaths per 1, 000), and among race/ethnic groups (between Black and White Brazilians from 1.0 to 0.8 deaths per 1, 000). Even a 40 percentage point increase in coverage, however, would be insufficient to reach SDG targets alone, as it would be expected to reduce premature mortality from non-communicable diseases by 20% (vs the target of 33%), and communicable diseases by 15% (vs 100%). Conclusions: FHS primary care coverage may be critically beneficial to reducing within-country health inequalities, but reaching SDG targets will likely require coordination between primary care and other sectors.